2004
DOI: 10.1161/01.hyp.0000119191.33112.9c
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Culture of Arterial Smooth Muscle Cells From Human Placenta

Abstract: Abstract-A simple and economical technique was developed to isolate and culture human arterial smooth muscle cells from chorionic plate vessels. Placentas from healthy women were collected at the time of term delivery. Chorionic plate arteries were identified, excised, and cut into small pieces. An explant technique was used to grow cultures of placental arterial smooth muscle (PASM) cells. Small pieces of vessel with lumens down were placed in 100-mm culture plates and grown in Dulbecco modified eagle medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 9 publications
1
40
0
Order By: Relevance
“…To test this hypothesis, we examined the effects of neutrophils and their soluble products (ie, TNF-␣ and ROS) on extracellular matrix protein gene expression using primary cultures of human VSMCs, an in vitro model previously validated. 24 Analysis of the extracellular matrix gene array of VSMCs after overnight treatments showed a similar expression profile as that observed in blood vessels from preeclamptic women (see Supplemental Tables S2-S4 at http://ajp.amjpathol.org), including the upregulation of MMP1 and the down-regulation or no change of TIMP1 and COL1A1 gene expression. Realtime RT-PCR confirmed that neutrophils, TNF-␣, and ROS significantly up-regulated MMP-1 expression in VSMCs by 6-fold (P ϭ 0.05), 9-fold (P ϭ 0.028), and 19-fold (P ϭ 0.001), respectively, compared with controls.…”
Section: Neutrophils Tnf-␣ and Ros Increase Expression And Secretiomentioning
confidence: 55%
See 1 more Smart Citation
“…To test this hypothesis, we examined the effects of neutrophils and their soluble products (ie, TNF-␣ and ROS) on extracellular matrix protein gene expression using primary cultures of human VSMCs, an in vitro model previously validated. 24 Analysis of the extracellular matrix gene array of VSMCs after overnight treatments showed a similar expression profile as that observed in blood vessels from preeclamptic women (see Supplemental Tables S2-S4 at http://ajp.amjpathol.org), including the upregulation of MMP1 and the down-regulation or no change of TIMP1 and COL1A1 gene expression. Realtime RT-PCR confirmed that neutrophils, TNF-␣, and ROS significantly up-regulated MMP-1 expression in VSMCs by 6-fold (P ϭ 0.05), 9-fold (P ϭ 0.028), and 19-fold (P ϭ 0.001), respectively, compared with controls.…”
Section: Neutrophils Tnf-␣ and Ros Increase Expression And Secretiomentioning
confidence: 55%
“…24 The cells were treated for 24 hours with ROS generated by the oxidation of 0.05-mmol/L hypoxanthine (Sigma, St Louis, MO), 0.003-U/ml xanthine oxidase (Calbiochem, La Jolla, CA), 1-ng/ml TNF-␣ (R&D Systems, Minneapolis, MN), or neutrophils activated with 50-mol/L arachidonic acid (Cayman Chemical, Ann Arbor, MI) in a 1:16 ratio of neutrophils/VSMCs. Hypoxanthine plus xanthine oxidase generates superoxide that quickly dismutates to hydrogen peroxide, the physiological signaling molecule.…”
Section: Vsmc Culture and Treatmentmentioning
confidence: 99%
“…Primary single PVSMCs were isolated as previously described (22,23). Briefly, the portal vein was dissected under sterile conditions.…”
Section: Methodsmentioning
confidence: 99%
“…#03-031), and all samples were processed within a few hours of operation. SMCs were isolated using the explant method (Leik et al, 2004). Cells were isolated on the same day the surgery was performed.…”
Section: Aortic Tissue and Cell Culturementioning
confidence: 99%
“…SMCs were isolated from aortic tissue via the explant technique (Leik et al, 2004) and maintained under cell culture conditions until growth was observed ( Figure 1A). During initial experiments, cells were explanted in DMEM/F12 supplemented with 10% fetal bovine serum.…”
Section: Sample Characterizationmentioning
confidence: 99%